Excellent Service Based on Human Capital and Leader Mindfulness (Survey of Sharia Hotel Employees in Bandung) - Tatiek Ekawati Permana; Tjutju Yuniarsih; Eeng Ahman; Rofi Rofaida (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Human resources have a very important role in providing services, especially those that are interpersonal or require empathy. The hotel industry, which is closely related to service, is the object of this research because there are still many complaints. Service complaints including 3A (attitude, attention, and action) remain a highlight that still needs to be improved. This research aims to analyze how human contribution as company capital with the support of leaders continues to improve service quality. The research uses a quantitative approach, with an explanatory survey method. The population determined was employees of the Syariah Hotel in Bandung using random sampling. The data collection tool is a questionnaire with a Likert scale which is distributed online to Syariah Hotel employees in Bandung. The research results show that human capital contributes positively to leader mindfulness. Human capital contributes positively to excellent service, and leader mindfulness contributes positively to excellent service. The research has implications for prioritizing human capital development and cultural awareness across organizations for sustainable business.